2017
DOI: 10.1167/17.14.11
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of perceptual and cognitive functions involved in useful-field-of-view test performance

Abstract: The useful-field-of-view (UFOV) test measures the amount of information someone can extract from a visual scene in one glance. Its scores show relatively strong relationships with everyday activities. The UFOV test consists of three computer tests, suggested to measure processing speed and central vision, divided attention, and selective attention. However, other functions seem to be involved as well. In order to investigate the contribution of these suggested and other perceptual and cognitive functions, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
(44 reference statements)
5
24
0
Order By: Relevance
“…In addition to visual functions, the age-related decline of UFOV3 performance could also be related to higher cognitive processes. Previous research has shown many correlations between UFOV3 performance and other cognitive tasks including general cognition, executive functioning and change detection (e.g., [ 10 ], for a summary see [ 11 ]). Although we excluded participants who reported the presence of a neurological disorder, we did not screen the general cognitive abilities of the subjects explicitly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to visual functions, the age-related decline of UFOV3 performance could also be related to higher cognitive processes. Previous research has shown many correlations between UFOV3 performance and other cognitive tasks including general cognition, executive functioning and change detection (e.g., [ 10 ], for a summary see [ 11 ]). Although we excluded participants who reported the presence of a neurological disorder, we did not screen the general cognitive abilities of the subjects explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…Values are listed under r[ci] . We used a random effects analysis to estimate the true underlying effect size and its 95% confidence interval which is depicted here as the polygon using R version 3.1.2 [ 38 ] with the ‘metafor’ package [ 54 ](for more details, see [ 11 ]). [ 55 ].…”
Section: Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Stroke Association guidelines for the early management of acute ischemic stroke assessment emphasize testing of the level of consciousness, motor strength, items relating to confrontation visual field measurements, horizontal eye movements and visual inattention (4). However, visual function per se is seldom examined rigorously in the emergency room or during initial hospitalization for stroke (5), despite the central role vision plays in driving most human brain functions such as eye movements (6), attention (7), cognition (8), emotional responses (9), motor actions (6), and occupying larger volumes of cortical and subcortical regions in the human brain than do motor functions (10,11).…”
Section: Introductionmentioning
confidence: 99%